Absence of bones in archaeological sites from the southeast of Uruguay: Taphonomy or human behavior?. Issue 4 (14th February 2022) - S. Villagran, Ximena; Rodriguez, Mauricio; Pereira, Heinkel Bentos; Gianotti, Camila; Sotelo, Moira; del Puerto, Laura
Abstract: The rework of daily refuse, including large quantities of faunal remains, is a common explanation for earthen mound construction in the Uruguayan lowlands, which started about 5000 years ago. While some earthen mounds contain human and animal bones in high abundance, several others contain only a few fragments. Thousands of years later (17th to 18th centuries), stone structures known as cairns were used in the same region and are believed to have served as the burial ground for local chiefs. However, no bone remains were ever found during excavations. The acidity of local soils has been the common explanation for the low frequency and/or complete absence of bone remains in earthen mounds and cairns. To investigate the absence of bones possibly induced by a corrosive environment, we applied Fourier transform infrared spectroscopy (FTIR), X‐ray powder diffraction (XRPD), and micromorphology to study the sediments at three sites: (1) an earthen mound rich in macroscopic bone fragments (CH2D01 site—CH); (2) an earthen mound with only a few macroscopic bone fragments (Las Palmas—LP); and (3) sediments from beneath a cairn with no macroscopic bone remains (Mario Chafalote cairn—MC). FTIR and XRPD showed the existence of burnt bones at the CH mound and a complete absence of bone mineral at LP and MC. Micromorphology revealed that, though invisible in the FTIR spectra, the LP mound contains micro‐bone fragments, but in extremely low frequency. Analyses indicate that taphonomy did not play a major role in the low frequency or absence of bones at the LP and MC sites, located in a similar environmental context, and that differences in site use and mound technology explain the contrasting composition of the CH mound.